2018
DOI: 10.3390/ijms19041044
|View full text |Cite
|
Sign up to set email alerts
|

Feature Tracking for High Speed AFM Imaging of Biopolymers

Abstract: The scanning speed of atomic force microscopes continues to advance with some current commercial microscopes achieving on the order of one frame per second and at least one reaching 10 frames per second. Despite the success of these instruments, even higher frame rates are needed with scan ranges larger than are currently achievable. Moreover, there is a significant installed base of slower instruments that would benefit from algorithmic approaches to increasing their frame rate without requiring significant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Hartman et al [40] designed a feedback-based feature tracking algorithm that reduces imaging time by focusing on the characteristics of the sample, thus reducing the total imaging area. The Hartman team used the same parameters to perform comparative tests on circular gratings, square gratings, silicon steps as well as DNA strands and found that the imaging time of raster scanning was reduced by 3-12 times.…”
Section: Improvements Of Hs-afm Imaging Functionmentioning
confidence: 99%
“…Hartman et al [40] designed a feedback-based feature tracking algorithm that reduces imaging time by focusing on the characteristics of the sample, thus reducing the total imaging area. The Hartman team used the same parameters to perform comparative tests on circular gratings, square gratings, silicon steps as well as DNA strands and found that the imaging time of raster scanning was reduced by 3-12 times.…”
Section: Improvements Of Hs-afm Imaging Functionmentioning
confidence: 99%
“…The probe is then moved along that predicted path and feedback used to correct any prediction error. The method has been used to image DNA (Hartman and Andersson 2018) and to quickly build contour maps of cells (Zhang et al 2015a). Because it naturally eliminates drift in the microscope over time, the method will likely be particularly beneficial to examine samples over long periods of time.…”
Section: Feature-trackingmentioning
confidence: 99%
“…(c) Experimental image of a strand of DNA acquired using a feature-tracking method known as local circular scan. Image reproduced with permission from (Hartman and Andersson 2018) to increase probe speed or improve the system hardware.…”
Section: Feature-trackingmentioning
confidence: 99%
“…Non-raster scan patterns can also improve imaging rate by reducing sampling rather than increasing speed. This class includes local scanning methods that use the measurements in real-time to steer the tip to focus the scan on features of interest [26]- [29]. While these have been shown to yield an order of magnitude or better improvement in imaging rate, they are limited in the class of samples that can be imaged and do not produce a full image with all the context.…”
Section: Introductionmentioning
confidence: 99%